Nano/meso/macroporous materials characterization affected by experimental conditions and features of the used methods - V. M. Gun'ko (Хімія, фізика та технологія поверхні)
The aim of this study was to analyze a set of methods: adsorption, X-ray, microscopic, cryoporometry, relaxometry, and thermoporometry used to investigate the morphological and textural characteristics of materials being in vacuum, or gaseous or liquid dispersion media, as well the interfacial phenomena basic for the used approaches. Techniques used in the studies should be divided into eight groups: (i) adsorption-desorption of low-molecular weight probe compounds (N2, Ar, etc.); (ii) adsorption or confinement of low- or high-molecular weight compounds in pores (voids) of solid particles being in liquid media; (iii) small angle X-ray scattering (SAXS) or small angle neutron scattering (SANS); (iv) quantitative analysis of images recorded using microscopic methods (TEM, SEM, AFM), etc.; (v) thermoporometry based on differential scanning calorimetry (DSC) with decreasing-increasing temperature utilizing melting thermograms; (vi) cryoporometry based on low-temperature 1H NMR spectroscopy giving the dependence of signal intensity on temperature; (vii) relaxometry based on NMR spectroscopy dealing with transverse relaxation time vs. temperature; and (viii) relaxometry based on thermally stimulated depolarization current (TSDC) measurements related to dipolar and dc relaxations. Each method could be characterized by systematic errors caused by many factors. However, the use of a set of the aforementioned methods in parallel can allow one to elucidate the reasons and level of these systematic errors that is of importance for correct characterization of the materials studied. Thus, the larger the number of methods used in parallel, the more comprehensive the morphological and textural characterization of the adsorbents.